Hr Management In Intellectual Property Implementation In Tasikmalaya City - Fitriansyah Fitriansyah; Dedi Rianto Rahadi; Nurlia Nurlia; Akhmad Baidun (International Journal of Economics and Management Research, 2023)
2022 will be the rise of Micro, Small and Medium Enterprises (MSMEs) in Indonesia by contributing 61% of the national GDP and absorbing 97% of the total workforce. Based on the city area, UMKM is one of the components that contributes 9.27 % of economic growth in Pangkal Pinang City. However, the application of Intellectual Property (IP) in MSME business behavior has not been handled optimally. The purpose of this study is to identify human resource management in MSME actors in building work teams that are aware of IP in business activities. This research using a qualitative-descriptive approach. Data were obtained by conducting observations and interviews with MSME business actors in Tasikmalaya City who had not registered or had registered their KI. The results of the study show that SMEs have an awareness of the importance of IP in entrepreneurship. KI is assessed by MSME actors as supporting business continuity through the maturation of the three entrepreneurial teams they have. MSMEs in Tasikmalaya City have at least a production team, operational team and marketing team. The three teams currently being developed are the marketing team, because they involve digital media capabilities. That is, the application of IP is a priority to avoid claims on the brand or type of business they own. In addition, MSME actors utilize family-based human resources. This character is in accordance with the application of the Pancasila economy.